Posterior reversible encephalopathy syndrome: a case report and review of the literature - Urbonaitė , G. V.; Audronytė , E.; Valaikienė , J. (Neurologijos seminarai, 2020)
Posterior reversible encephalopathy syndrome (PRES) is a rare condition that is diagnosed based on clinical and radiological findings. Usually this condition manifests with acute neurological symptoms, such as headache, impaired consciousness, seizures and/or vision disturbances with fluctuations in arterial blood pressure, and neuroimaging abnormalities of bilateral subcortical vasogenic edema, usually seen in occipital lobes. The pathophysiology of this syndrome is still debated, however, it is thought that PRES develops due to the endothelial dysfunction. PRES should be suspected when acute neurological symptoms develop in patients with renal insufficiency, arterial hypertension or fluctuations in blood pressure, eclampsia, sepsis, and autoimmune diseases who are taking immunosupressive or citotoxic medications. The main treatment consists of the removal of the precipitating factors (correction of arterial hypertension, cessation of immunosupressive treatment or dose reduction). The prognosis is usually good, with a regresion in clinical and radiological symptoms and signs in several days or weeks. Very rarely, PRES can have complications like intracerebral hemmorhage, severe brain edema, and fatal outcome or persisting disability. In this article, we present a rare clinical case when PRES was diagnosed accidentally during a follow-up head magnetic resonance imaging of meningioma. The patient, who had suffered from chronic headaches for several years, had arterial hypertension with fluctuations in blood pressure. Typical radiological signs of PRES remained visible after 1, 3 and 6 months and completely regressed after a year.